Fungal Periprosthetic Joint Infection of Hip – Report of 2 Cases - Ho, Sheung Tung (Orthop J Sports Med, 2020)
A 72-year old woman had revision unipolar hemiarthroplasty for AMA loosening with vertical split fracture of greater trochanter. This was complicated by PJI, treated with staged arthroplasty with articulated antibiotic loaded cement spacer. Revision of antibiotic loaded cement spacer for dislocation and cable plate fixation of greater trochanter was done. Then the tissue specimen grew Candida ablicans. Fluconazole was given. Repeated debridement and exchange of antibiotic loaded cement spacer was done twice again with amphoteric B and vancomycin added to the cement. Unfortunately, the frozen section was still positive despite the CRP was returned to normal for 1 month. Oral fluconazole was continued. Finally, revision total hip replacement was done 14 months after the initial insertion of antibiotic loaded cement spacer. The patient could manage to walk with frame indoor with no hip pain at 3 year follow-up. Another 80-year old woman had removal of AMA, debridement and antibiotics loaded cement spacer was done for PJI. This was complicated by breakage of the articulated cemented spacer during reduction and later hip dislocation despite of cemented acetabular liner. A total of 3 debridement and antibiotics loaded cement spacer were done. Besides Candida albicans, tissue also grew Enterobacter cloacae and Pseudomonas aeruginosa. Exchange of cement space loaded with gentamicin and voriconazole was done as the 4th reoperation 22 weeks after the debridement and antibiotics loaded cement spacer insertion. Intraoperatively, the patient developed haemorrhagic shock and complicated with myocardial infraction and pneumonia postoperatively and eventually succumbed 12 days after the last operation. The control rate of fungal PJI of only 36% was reported in the literature. The use of systemic and local antifungal agents, surgical treatment strategy and outcomes will be reviewed.